2017
DOI: 10.1186/s12957-016-1095-y
|View full text |Cite
|
Sign up to set email alerts
|

TPX2 expression is associated with poor survival in gastric cancer

Abstract: BackgroundTargeting protein for Xenopus kinesin-like protein 2 (TPX2) is a microtubule-associated protein required for microtubule formation in human cells. Several studies have demonstrated that TPX2 is overexpressed in multiple tumor types and promotes tumor growth and metastasis. However, there have been few reports regarding its role in gastric cancer. In this study, we evaluated TPX2 expression and investigated its correlations with gastric cancer clinicopathological features and prognosis.MethodsTumor sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 24 publications
1
65
0
Order By: Relevance
“…Targeting protein for Xenopus kinesin-like protein 2 (TPX2), which is considered to be a microtubuleassociated protein, can participate in the activation of protein kinase activity, regulation of mitotic spindle tissue, apoptotic processes, mitosis, cell division and cell proliferation [25,26]. Previous studies have shown that TPX2 is overexpressed in tumour tissues and promotes the tumorigenesis of multiple cancers [27][28][29]. In breast cancer cells, TPX2 promotes cancer cell invasion and migration via regulating MMP2 and MMP9 expression [30].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting protein for Xenopus kinesin-like protein 2 (TPX2), which is considered to be a microtubuleassociated protein, can participate in the activation of protein kinase activity, regulation of mitotic spindle tissue, apoptotic processes, mitosis, cell division and cell proliferation [25,26]. Previous studies have shown that TPX2 is overexpressed in tumour tissues and promotes the tumorigenesis of multiple cancers [27][28][29]. In breast cancer cells, TPX2 promotes cancer cell invasion and migration via regulating MMP2 and MMP9 expression [30].…”
Section: Discussionmentioning
confidence: 99%
“…(Jagarlamudi et al, 2015 ; Du et al, 2016 ); Targeting protein for Xenopus kinesin-like protein 2 (TPX2) is microtubule-associated protein and impacts spindle assembly in human cells (Huang et al, 2014 ), and previous studies proved that TPX2 expression was associated with poor survival in gastric cancer, breast cancer, colon cancer and esophageal cancer, etc. (Wei et al, 2013 ; Liu et al, 2014 ; Yang et al, 2015 ; Tomii et al, 2017 ); The cell division cycle associated 8 (CDCA8) gene encodes a component of the chromosomal passenger complex and plays an important role in mitosis, and overexpression of CDCA8 was reported in some human cancers, demonstrating that CDCA8 was required for the growth and progression of several cancers such as breast cancer, gastric cancer, lung carcinogenesis (Hayama et al, 2007 ; Yan et al, 2012 ; Jiao et al, 2015 ); Several studies demonstrated the AEBP1 upregulation conferred acquired resistance to BRAF (V600E) inhibition in melanoma and was associated with bad survivals of patients with glioma (Ladha et al, 2012 ; Hu et al, 2013 ); The protein encoded by FOXM1 is phosphorylated in M phase and regulates the expression of several cell cycle genes, such as cyclin B1 and cyclin D1, and previous studies suggested that FOXM1 promoted tumor progression of multiple cancers including gastric cancer, ovarian cancer, cervical cancer, colorectal cancer and breast cancer, etc. Trichostatin A potentiates TRAIL-induced antitumor effects via inhibition of ERK/FOXM1 pathway in gastric cancer (Barger et al, 2015 ; Yau et al, 2015 ; Zheng et al, 2015 ; Li et al, 2016 ; Wang et al, 2016 ; Song et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of TPX2 has been observed in lung cancer, hepatic cancer, colon cancer [28][29][30]. Moreover, TPX2 is also a marker of poor tumor prognosis in several cancers [31]. Both CDC20 and TPX2 were related to the process of cell cycle [32].…”
Section: Discussionmentioning
confidence: 99%